2011
DOI: 10.1021/es103692f
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of Aerosol Chemistry during New Particle Formation Events at a Remote Rural Mountain Site

Abstract: Determining the major sources of particles that act as cloud condensation nuclei (CCN) represents a critical step in the development of a more fundamental understanding of aerosol impacts on cloud formation and climate. Reported herein are direct measurements of the CCN activity of newly formed ambient particles, measured at a remote rural site in the Sierra Nevada Mountains of Northern California. Nucleation events in the winter of 2009 occurred during two pristine periods following precipitation, with higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
71
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(82 citation statements)
references
References 58 publications
11
71
0
Order By: Relevance
“…Creamean et al reported an amine-OC particle burst episode with decreased mean particle sizes after a precipitation in Northern California, which was explained by amine-assisted particle growth after a particle nucleation event. [29] Precipitation can effectively remove airborne particles and leave a pristine ambient environment with less surface area, which is favoured for particle nucleation. However, new particle formation processes cannot explain our observation.…”
Section: Particulate Amine Burst Episodesmentioning
confidence: 99%
See 3 more Smart Citations
“…Creamean et al reported an amine-OC particle burst episode with decreased mean particle sizes after a precipitation in Northern California, which was explained by amine-assisted particle growth after a particle nucleation event. [29] Precipitation can effectively remove airborne particles and leave a pristine ambient environment with less surface area, which is favoured for particle nucleation. However, new particle formation processes cannot explain our observation.…”
Section: Particulate Amine Burst Episodesmentioning
confidence: 99%
“…[13,[18][19][20] De Haan et al [21,22] observed that reactions between glyoxal and amines or amino acids can produce light-absorbing, nitrogen-containing imidazoles and oligomers. Particle phase amines have been extensively observed in many areas [9,17,[23][24][25] especially in ultrafine particles during nucleation [26][27][28] and particle growth [29] events. Compared with ammonia, amines have higher molecular weights and present stronger alkalinity that make them perfect candidates in new particle formation and growth.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…in the continental boundary layer have been reported 17,19,20 , suggesting that sulphuric acid-amine nucleation is likely to be an important atmospheric process. However, atmospheric observations indicate both the presence 10,11,16 and the absence 22 of a significant amine fraction in newly formed particles, which suggests considerable variability of ambient amine levels. Although amines are volatile vapours, our measurements show that sulphate particles constitute an almost perfect sink (negligible evaporation).…”
mentioning
confidence: 99%